Circular Network of Coregulated Sphingolipids Dictates Chronic Hypoxia Damage in Patients With Tetralogy of Fallot - Zhou, Na; Liu, Libao; Zou, Rongjun; Zou, Minghui; Zhang, Mingxia; Cao, Fan; Liu, Wenhua; Yuan, Huili; Huang, Guodong; Ma, Li; Chen, Xinxin (Frontiers in Cardiovascular Medicine, 2022)
Background: Tetralogy of Fallot (TOF) is the most common cyanotic heart disease. However, the association of cardiac metabolic reprogramming changes and underlying molecular mechanisms in TOF-related chronic myocardial hypoxia damage is still unclear. Methods: Here, we combined microarray transcriptomics analysis with LC–MS/MS spectrum metabolomics analysis to establish the metabolic reprogramming that occurs in response to chronic hypoxia damage. Two GEO datasets, GSE132176 and GSE141955, were downloaded to analyze the metabolic pathway in TOF. Then, a metabolomics analysis of the clinical samples (right atrial tissue and plasma) was performed. Additionally, an association analysis between differential metabolites and clinical phenotypes was performed. Next, four key genes related to sphingomyelin metabolism were screen, and their expression was validated by QT-PCR. Results: The GSEA showed that sphingolipid metabolism was downregulated in TOF, and the metabolomics analysis showed that multiple sphingolipids were dysregulated. Additionally, genes related to sphingomyelin metabolism were identified. We found that four core genes, UGCG, SGPP2, FA2H and SGPP1, were downregulated in TOF. Conclusion: Sphingolipid metabolism was downregulated in TOF; however, the detailed mechanism needs further investigation.